PH and redox triggered doxorubicin release from covalently linked carbon dots conjugates. Issue 10 (10th March 2021) - Hettiarachchi, Sajini D.; Kirbas Cilingir, Emel; Maklouf, Heidi; Seven, Elif S.; Paudyal, Suraj; Vanni, Steven; Graham, Regina M.; Leblanc, Roger M.
Abstract : Tumor microenvironment responsive drug delivery systems are potential approaches to reduce the acute toxicity caused by high-dose cancer chemotherapy. Abstract : Tumor microenvironment responsive drug delivery systems are potential approaches to reduce the acute toxicity caused by high-dose cancer chemotherapy. Notwithstanding the conventional nano-drug delivery systems, the redox and pH stimuli drug delivery systems are currently gaining attention. Therefore, the current study was designed to compare three different covalent carbon dots (C-dots) systems based on doxorubicin (dox) release profiles and cancer cell viability efficacy under acidic and physiological conditions. The C-dots nanosystems that were examined in this study are directly conjugated (C-dots-dox), pH triggered (C-dots-HBA-dox), and the redox stimuli (C-dots-S–S-dox) conjugates. The drug loading content (DLC%) of the C-dots-S–S-dox, C-dots-HBA-dox, and C-dots-dox was 34.2 ± 0.4, 60.0 ± 0.3, and 70.0 ± 0.2%, respectively, that examined by UV-vis spectral analysis. The dox release paradigms were emphasized that all three conjugates were promisingly released the dox from C-dots faster in acidic pH than in physiological pH. The displayed highest dox released percentage in the acidic medium was 74.6 ± 0.8% obtained by the pH stimuli, C-dots-HBA-dox conjugate. When introducing the redox inducer, dithiothreitol (DTT), preferentially, the redox stimuli C-dot-S–S-dox conjugate demonstrated a faster dox release at acidic pH than in the pH 7.4. The SJGBM2 cell viability experiments revealed that the pH stimuli, C-dots-HBA-dox conjugate, displayed a significant cell viability drop in the artificially acidified pH 6.4 medium. However, in the physiological pH, the redox stimuli, C-dots-S–S-dox conjugate, was promising over the pH stimuli C-dots-HBA-dox, exhibiting cell viability of 60%, though its' efficacy dropped slightly in the artificially acidified pH 6.4 medium. Moreover, the current study illustrates the stimuli conjugates' remarkable efficacy on sustain drug release than direct amide linkage.